2003
DOI: 10.1037/0278-7393.29.6.1256
|View full text |Cite
|
Sign up to set email alerts
|

Masked Repetition and Phonological Priming Within and Across Modalities.

Abstract: Lexical decision latencies to word targets presented either visually or auditorily were faster when directly preceded by a briefly presented (53-ms) pattern-masked visual prime that was the same word as the target (repetition primes), compared with different word primes. Primes that were pseudohomophones of target words did not significantly influence target processing compared with unrelated primes (Experiments 1-2) but did produce robust priming effects with slightly longer prime exposures (67 ms) in Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
123
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(140 citation statements)
references
References 51 publications
12
123
2
3
Order By: Relevance
“…This claim is made by Perfetti and colleagues (e.g., Perfetti, Bell, & Delaney, 1988;Xu & Perfetti, 1999;Zhang, Perfetti, & Yang, 1999), Frost and colleagues (e.g., Gronau & Frost, 1997;Frost, 1998;2003), Grainger and colleagues (e.g., Ferrand & Grainger, 1992;Grainger, Diependaele, Spinelli, Ferrand, & Farioli, 2003), and Van Orden and colleagues (e.g., Van Orden, Pennington, & Stone, 1990;Ziegler, Van Orden, & Jacobs, 1997), among others (Brysbaert, 2001;Catena, Fuentes, & Tudela, 2002;Johnston & Castles, 2003;Lukatela Recoding & Turvey, 1994;Luo, Johnson, & Gallo, 1998). For example, Xu and Perfetti (1999) argue for "rapid automatic phonological activation, independent of stimulus based processing strategies" (p. 26).…”
Section: Phonological Recodingmentioning
confidence: 91%
“…This claim is made by Perfetti and colleagues (e.g., Perfetti, Bell, & Delaney, 1988;Xu & Perfetti, 1999;Zhang, Perfetti, & Yang, 1999), Frost and colleagues (e.g., Gronau & Frost, 1997;Frost, 1998;2003), Grainger and colleagues (e.g., Ferrand & Grainger, 1992;Grainger, Diependaele, Spinelli, Ferrand, & Farioli, 2003), and Van Orden and colleagues (e.g., Van Orden, Pennington, & Stone, 1990;Ziegler, Van Orden, & Jacobs, 1997), among others (Brysbaert, 2001;Catena, Fuentes, & Tudela, 2002;Johnston & Castles, 2003;Lukatela Recoding & Turvey, 1994;Luo, Johnson, & Gallo, 1998). For example, Xu and Perfetti (1999) argue for "rapid automatic phonological activation, independent of stimulus based processing strategies" (p. 26).…”
Section: Phonological Recodingmentioning
confidence: 91%
“…Figure 4 provides a tentative outline of these component processes and their possible interactions. The visual word recognition part of Figure 4 is taken from the bimodal interactive activation (BIA) model (Diependaele, Ziegler, & Grainger, in press;Grainger, Diependaele, Spinelli, Ferrand, & Farioli, 2003;Grainger & Ziegler, 2007;. Visual features map onto prelexical orthographic representations (not shown), which then map onto whole-word orthographic representations (O words) along the direct pathway to semantics and onto wholeword phonological representations (P words).…”
Section: Resultsmentioning
confidence: 99%
“…Although we aimed to account for this variance by introducing the control variable, residual measurement errors cannot be excluded. Given their more abstract origin, semantic transparency effects might be more vulnerable to this kind of noise (including noise from erroneous Grainger et al, 2003). These masks can induce stronger interference with the initial form encoding of primes than is usually the case when there is no backward masking (e.g., as in Forster & Davis, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Experiments 1 and 2 not only tested visual masked priming, but also masked cross-modal priming with visual primes and auditory targets (Grainger, Diependaele, Spinelli, Ferrand, & Farioli, 2003;Kouider & Dupoux, 2001). Our prior research (Diependaele et al, 2005) revealed that cross-modal transfer is effective with respect to morpho-orthographic activation in the case of suffixed words.…”
Section: Experiments 1 Methodsmentioning
confidence: 99%